P235 Vaginal and rectal m. genitalium (MG), c. trachomatis (CT), and n. gonorrhoeae (GC) co-infection among women in seattle, WA. (14th July 2019) - Khosropour, Christine; Golden, Matthew; Soge, Olusegun; Barbee, Lindley; Dombrowski, Julia; Leipertz, Gina; Unutzer, Anna; Manhart, Lisa
Abstract : Background: Rectal CT is increasingly recognized as a common infection among women, even in the absence of anal sex. Little is known about the prevalence or epidemiologic pattern of rectal MG and rectal MG/CT/GC co-infection among women. Methods: We recruited women at high risk for urogenital CT from the municipal STD clinic in Seattle, WA, 2017–2018 for a cohort study. Participants self-collected vaginal and rectal specimens for nucleic acid amplification testing (NAAT) for CT and GC. We retrospectively tested enrollment samples for vaginal and rectal MG using NAAT. We examined factors associated with rectal MG using logistic regression to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI). Results: Of 50 enrolled women, 13 (26%) tested positive for MG. Ten (20%) had vaginal MG and 11 (22%) had rectal MG. Eight (16%) women had concurrent vaginal and rectal MG, 3 (6%) had isolated rectal MG, and 2 (4%) had isolated vaginal MG. Among 10 women with vaginal MG, 3 (30%) also had vaginal CT but none had vaginal GC. Of 11 women with rectal MG, 4 (36%) also had rectal CT but none had rectal GC. Compared to women without rectal MG, women with rectal MG were more likely to be <25 years old (aOR=2.9; 95% CI=0.7–11.9), less likely to be White (aOR=0.22; 95% CI=0.03–1.8), and less likely to report anal sex in the past 12 months (aOR=0.41; 95% CI=0.08–2.2). No women with rectal MG reported anal symptoms. Conclusion: Rectal MG was common (prevalence=22%) among women at high risk for vaginal CT, but the majority of women with MG did not have CT or GC. Rectal MG was most often identified among women with vaginal MG, and was not significantly associated with reporting anal sex. The high prevalence of rectal MG merits further investigation to understand its natural history and clinical implications. Disclosure: No significant relationships.